ZnO/SiO2 Composite as Catalyst for the Transformation of Glycerol to Glycerol Carbonate - Krisnandi, Yuni Krisyuningsih; Eckelt, Reinhard; Atia, Hanan; Adam, Martin; Saragi, Indah Revita; Martin, Andreas; Richter, Manfred (UI Scholars Hub, 2020)
Zinc oxide/porous silica (ZnO/SiO2) composite was used as a catalyst to transform glycerol to glycerol carbonate (GC), a chemical intermediate and monomer for the synthesis of new functionalized polymers. The ZnO/SiO2 catalyst was prepared using the direct precipitation method by mixing zinc sulfate solution with Aerosil 300 silica suspension and adding potassium oxalate solution. Catalytic transformation used glycerol and urea (molar ratio = 1:1) at 140 °C, 40 mbar, and various reaction times (1–6 h). The ZnO catalyst exhibited a high percentage of glycerol conversion of 82.38%; however, the yield of GC and selectivity toward GC were relatively low (i.e., 33.33% and 40.46%, respectively). The presence of silica support (ZnO/(x)SiO2 increased the selectivity toward GC and yield of GC to 74.40% to 77.83% and 57.86% to 64.30%, respectively. Furthermore, although its crystallinity decreased, the reused ZnO/(60)SiO2 catalyst still exhibited a high activity. The scanning transmission electron microscopy image indicated the migration of ZnO on the surface of the composite and the possibility of ZnO-glycolate formation, which were also confirmed by FTIR measurement. Nevertheless, these results showed that ZnO/SiO2 is a promising catalyst for the transformation of glycerol to GC.